Smarter growth : activism and environmental policy in Metropolitan Washington - Spiers, John H. (City in the twenty-first century book series., 2018)
"Smarter Growth offers a fresh understanding of environmental politics in metropolitan America, using the Washington, D.C. area as a case study to demonstrate how public officials and their constituents engaged in an ongoing dialogue that positioned environmental protection as an increasingly important facet of planning and development."--